Capacity of Storage of Participant Cargoes - Abduvakhitov , Shakhboz (International Journal of Psychosocial Rehabilitation, 2020)
Warehouses located at points of transshipment of goods from one type of transport to another perform important functions of converting cargo flows with the goal of further most efficient transportation. When designing a piece-and-piece cargo warehouse, it is necessary to choose the best way to store goods, while ensuring the most complete filling of the warehouse area with goods, as well as the minimum costs when moving goods inside the warehouse. Mathematical models are proposed that establish the relationship between the individual parameters of the unit-cargo warehouse. The models were used in the study of the mutual influence of the parameters on each other; the storage capacities of packaged goods were also determined